Hoaxes in Islamic Perspective: Qur'anic Solutions for Building an Anti-Hoax Society - Murtiningsih; Adeoye, Moses Adeleke (Al-Karim: International Journal of Quranic and Islamic Studies, 2025)
This study aims to analyze the Islamic perspective on hoaxes and explore Qur'anic solutions for building a society resistant to misinformation. The phenomenon of hoaxes has existed throughout history, driven by various interests, as seen in the hadith al-ifk incident, where Siti Aisyah, the wife of the Prophet Muhammad, was falsely accused of adultery by hypocrites to divide the Muslim community. In the contemporary era, hoaxes have become deeply embedded in society due to the rapid dissemination of misinformation through social media, leading to significant individual and societal harm. This research employs a qualitative approach with a library research method, utilizing normative and sociological theological perspectives. The data collection technique follows a heuristic model, while data analysis is conducted using a descriptive approach. The findings indicate that the Qur'an provides clear guidance on countering hoaxes by emphasizing the obligation of tabayyun (verification) and ethical communication. The study also highlights that hoaxes not only harm individuals but also destabilize societal and state structures. Therefore, fostering an anti-hoax society requires internalizing Qur'anic ethical principles that encourage truthfulness, critical thinking, and responsible communication. Contribution: Theoretically, this research contributes to Islamic studies by integrating normative Qur'anic principles with contemporary social issues, demonstrating the Qur'an’s relevance in addressing modern challenges. Furthermore, the study offers practical insights for developing a resilient society capable of resisting the spread of misinformation.